Sheltie finds a friend - Clover, Peter (New York: Aladdin Paperbacks, 2000)
"Sheltie is very happy when Mudlark, Marjorie Wallace's donkey, comes to stay. But one morning Mudlark disappears. Only Sheltie seems to know what happened to him..."
Keywords: Donkeys -- Fiction; Shetland pony -- Fiction